Comparative Anatomical and Histological Study of Duodenum between Laughing Dove Streptopelia Senegalensis and White breasted Kingfisher, Halcyon Smyrnensis - Adnan W. Al-Bideri; Ali Nadeem Jawad (Al-Qadisiyah Journal of Pure Science, 2018)
This study used two groups of adult and healthy birds, joined the first group of 15 pigeons laughing doves granivores , five of them for the purpose of anatomical study, and another ten for the purpose of histological study, and included a second group of 15 birds Kingfisher white breasted  carnivores, and five of them for the purpose of anatomical study, and ten of them for the purpose of histological study.    The Anatomical study included the study of the form of duodenum position and shape in the laughing  dove and white breasted kingfisher birds, the histological study included histological structure of duodenum and  measuring the thickness of the wall consisting of duodenum.    The study have showed that the duodenum in both the birds is a single surround the pancreas and the results showed that the  villi which were longer and thicken and contain more branches in its base part in kingfisher copared with that of laughing dove bird which was shorter and thinner, It has been noted that there was differences in layer   thickness that form intestine wall .The mucosa layer was thinner compared with other layer.    It has been concluded that the difference of food type that the birds have can have clear effect in both morphological and histological structure of duodenum ; namely ,the thickness of layers that forms their walls.